2022
DOI: 10.1002/jsfa.11774
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin treatment reduces qualitative decay and improves antioxidant system in highbush blueberry fruit during cold storage

Abstract: BACKGROUND: Blueberry is considered as a 'functional food' because it contains bioactive compounds such as flavonoids, phenolic acids, tannins and anthocyanins. The blueberry is one of the most consumed berries in the world and is highly appreciated by consumers because of its unique taste and sensory properties. Fresh blueberries decay rapidly because of mould and water loss. To preserve the qualitative and nutraceutical traits of fresh highbush blueberries during storage, the efficacy of 1 mM melatonin treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Wei et al [ 93 ] found that MT treatment helps protect against subcellular decompartmentalization in rambutan pericarp, thereby reducing enzymatic browning. Magri et al [ 86 ] reported that LOX-driven lipid peroxidation produces MDA and H 2 O 2 , leading to cellular degradation and fruit discoloration. However, highbush blueberries treated with melatonin exhibit reduced MDA and H 2 O 2 , suggesting minimized cellular harm and browning from decreased PPO and LOX activities during cold storage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wei et al [ 93 ] found that MT treatment helps protect against subcellular decompartmentalization in rambutan pericarp, thereby reducing enzymatic browning. Magri et al [ 86 ] reported that LOX-driven lipid peroxidation produces MDA and H 2 O 2 , leading to cellular degradation and fruit discoloration. However, highbush blueberries treated with melatonin exhibit reduced MDA and H 2 O 2 , suggesting minimized cellular harm and browning from decreased PPO and LOX activities during cold storage.…”
Section: Resultsmentioning
confidence: 99%
“…CMC-Gel samples performed slightly b than the control samples, which might be due to the ability of structural strengthenin the coating polymers. Magri et al [86] tested the efficiency of CMC-based composite ing, and their study effectively controlled the LOX activity in the minimally proce apple fruit under chilling conditions. MT ability to interact directly with the hydroph lipid phase of cell membranes due to its lipid solubility and potential to alter PLD f tionality may be key factors in controlling PLD activity and pericarp cellular damage contributes to the reduction in LOX activity mainly through its antioxidant prope modulation of gene expression, direct regulation of enzyme activities such as PLD general alleviation of stress responses in plants [87].…”
Section: Browning Related Enzyme Activitiesmentioning
confidence: 99%
“…The total phenolic content (TP) was evaluated through the Folin–Ciocâlteu method described by Magri and Petriccione [ 61 ] and expressed as mg of gallic acid equivalent (GAE) per 100 g −1 FW.…”
Section: Methodsmentioning
confidence: 99%
“…The reaction mix was incubated for 2 h in a dark room, after which absorbance at 765 nm was recorded. Results were calculated by using a calibration curve obtained though standard concentrations of gallic acid and expressed as mg of gallic acid equivalent (GAE) per 100 g −1 FW [ 50 ].…”
Section: Methodsmentioning
confidence: 99%